CONCEPTUAL METAPHOR WITHIN INVARIANT MEANING: THE LEARNING OF PHRASAL VERBS AMONG MALAYSIAN ESL LEARNERS - Subramaniam, Radika (PEOPLE: International Journal of Social Sciences, 2017)
his study intends to determine the invariant/core meanings of verbs and particles in isolation and see how these meanings motivate the distribution of messages in English phrasal verbs. It also aims to see if the exposure to the core meanings of the individual items that make up a phrasal verb (i.e. verb and particle) helps Malaysian learners to use phrasal verbs appropriately in English writings. The linguistic data were extracted from the BNC corpus. Tobin (1990)’s concept of invariant meaning and Lakoff & Johnson (1980)’s notion of Conceptual Metaphor were used to determine the core meanings of the verbs and particles. The analyses showed that the identification of single invariant meaning of the verbs and particles is important as they contribute to the realisation of different senses of phrasal verbs. These invariant meanings were then applied as treatment with fifteen students in the experimental group whereas another group of fifteen students which was assigned as the control group was engaged into traditional instruction by providing the meanings of the phrasal verbs extracted from the Oxford Phrasal Verbs Dictionary. The inferential analyses through paired samples t-test and independent samples t-test for the taught items indicate that although both groups performed significantly better in post-tests compared to pre-tests, the experimental group which received the semantic-based explicit (verbs and particles in phrasal verbs) instruction outperformed (significantly) the control group which received traditional instruction. Article DOI: https://dx.doi.org/10.20319/pijss.2018.33.16371657 This work is licensed under the Creative Commons Attribution-Non-commercial 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by-nc/4.0/ or send a letter to Creative Commons, PO Box 1866, Mountain View, CA 94042, USA.